Learning About Reflection of Light Based Ultraviolet Detection System Using Raspberry Pi - Nugroho Adi Pramono; Bertha Anggita Purwandani; Fauzan Ibnu Sofyan; Octavia Ghaisyani (Universitas Syiah Kuala, 2021)
Ultraviolet light is an electromagnetic radiation that has range of wavelengths between 100nm to 400nm. This wavelength can be identified by the ultraviolet index, where at this wavelenght ultraviolet light has an impact to human health. Ultraviolet light with ultraviolet index green to yellow is benefical for human health. Meanwhile, ultraviolet rays with red to purple ultraviolet index are harmful to human health. Ultraviolet rays that are harmful to humans can pass the surface of the earth caused by many factors, one of which is global warming. Therefore, this research was conducted to create an ultraviolet light detection system using Raspberry Pi as a sensor data reader and aims to learn about how much light reflected on the surface of the earth. The data obtained will be processed using the phyton programming language and presented using an LCD touchscreen. From this research, the values of the ultraviolet index from zero to six were obtained based on the ultraviolet index value from the BMKG indicate the categories of ultraviolet light associated with light reflection on the surface of the earth are known. So it can be concluded that the less ultraviolet light on the surface of the earth will be reflected easily by the earth, and the more ultraviolet light on the surface of the earth will be difficult to reflect.